The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2003
DOI: 10.1007/s00705-003-0011-2
|View full text |Cite
|
Sign up to set email alerts
|

Sequence and genetic arrangement of the U L region of the monkey B virus ( Cercopithecine herpesvirus 1) genome and comparison with the U L region of other primate herpesviruses

Abstract: The complete DNA sequence of the unique long (U(L)) region of monkey B virus (BV) was determined. Based on sequence homology and the presence of transcriptional control element motifs, homologues of every open reading frame present in the U(L) region of the Human herpesvirus 1 (herpes simplex virus 1, HSV-1) and Human herpesvirus 2 (herpes simplex virus 2, HSV-2) genomes were identified in BV. The BV genes are arranged in the same order and orientation as in HSV. These results demonstrate that the BV U(L) regi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 39 publications
1
17
0
Order By: Relevance
“…The sequences of the cloned fragments were identical to the genomic sequences of the corresponding B virus genes (42), with the exception of the mgG fragment, as there was a 132-bp deletion (positions 1096 to 1227 in the gG gene) in the constructed mgG donor plasmid. This deleted DNA fragment, which encodes a PAPTTT amino acid repeat, is present in the gG sequence of the E2490 strain but is not found in any of the other sequenced gG genes of B virus clinical isolates (40). Since the deletion construct encodes an mgG protein that actually mimics those produced during natural infections, we decided to use this construct for production of the mgG recombinant baculovirus.…”
Section: Resultsmentioning
confidence: 99%
“…The sequences of the cloned fragments were identical to the genomic sequences of the corresponding B virus genes (42), with the exception of the mgG fragment, as there was a 132-bp deletion (positions 1096 to 1227 in the gG gene) in the constructed mgG donor plasmid. This deleted DNA fragment, which encodes a PAPTTT amino acid repeat, is present in the gG sequence of the E2490 strain but is not found in any of the other sequenced gG genes of B virus clinical isolates (40). Since the deletion construct encodes an mgG protein that actually mimics those produced during natural infections, we decided to use this construct for production of the mgG recombinant baculovirus.…”
Section: Resultsmentioning
confidence: 99%
“…Sequence analysis of the partial U S regions of B virus and simian agent 8 virus demonstrated that human and primate viruses are colinear in this genomic segment (51). However, only a limited number of B virus gene sequences from the U L region have been published (3,36,62,63), and nothing has been reported about the structure and the gene content of the repeat genomic elements.…”
mentioning
confidence: 99%
“…It is important to recognize that the RXP-containing proteins are otherwise unrelated, as SM, in fact, shows structural and functional homology to an additional alphaherpesvirus protein, the herpes simplex virus ICP27 polypeptide (2,3,8,13,18,42,45). Similar transactivator proteins encoded by other herpesviruses do not contain an RXP repetitive element, and Us11-homologous proteins are found only in HSV-1, HSV-2, and the simian B virus (16,31,35). Importantly, however, several human herpesviruses are known to encode activities that can regulate PKR activation regardless of whether they produce an RXPcontaining protein (5,10).…”
Section: Discussionmentioning
confidence: 99%
“…After rocking for 1 h at room temperature, the beads were collected by centrifugation, suspended in 0.1 ml of SMPB plus 3% fraction V bovine serum albumin, 0.5% Triton X-100, and 1 mM CaCl 2 and treated for 20 min at room temperature with 8 U of micrococcal nuclease per ml or 8 U of micrococcal nuclease, 50 g of RNase A, and 300 U of RNase T 1 per ml. 35 S-labeled PKR produced by translation in vitro according to the manufacturer's directions (wheat germ T7 TNT quick coupled transcription-translation system; Promega, Madison, Wis.) was likewise treated with nuclease at the conclusion of the synthesis reaction. Phenylmethylsulfonyl fluoride was then added to both the beads loaded with GST fusion protein and the nucleasetreated in vitro translation reaction to a final concentration of 100 M. Then 1 l of the in vitro-translated lysate was added to the nuclease-treated beads containing bound fusion protein, and the final concentration of phenylmethylsulfonyl fluoride was brought to 200 M. Binding reaction mixtures were incubated at 30°C for 30 min and agitated manually every 5 min.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation